ANALISIS RISK DAN RETURN REKSADANA SAHAM DIBANDINGKAN DENGAN PORTFOLIO SAHAM SECARA ACAK - Mirna Mirna; Oktafalia Marisa Muzammil (Business Management Journal, 2017)
The research was conducted on the data listed in Indonesia Stock Exchange (BEI) in 2008-2010. This research aims to determine the risk and return’s difference between Mutual Funds Risk and Portfolio shares listed on the Stock Exchange. The research method used in this research is descriptive method using Kolmogorov Smirnov normality test and Non parametric: Mann Whitney. The results obtained by SPSS output is there is no difference between the shares of the Mutual Fund Return Portfolio randomly selected stocks, meanwhile there is a difference between the risk of stock mutual funds with random stock portfolio. Key Words- Mutual Funds Risk, Mutual Funds Return, Stock Exchange